Gigahertz-peaked spectra pulsars in Pulsar Wind Nebulae. Issue 2 (14th December 2017) - Basu, R; Rożko, K; Kijak, J; Lewandowski, W
Abstract: We have carried out a detailed study of the spectral nature of six pulsars surrounded by pulsar wind nebulae (PWNe). The pulsar flux density was estimated using the interferometric imaging technique of the Giant Metrewave Radio Telescope at three frequencies 325, 610, and 1280 MHz. The spectra showed a turnover around gigahertz frequency in four out of six pulsars. It has been suggested that the gigahertz-peaked spectrum (GPS) in pulsars arises due to thermal absorption of the pulsar emission in surrounding medium like PWNe, H ii regions, supernova remnants, etc. The relatively high incidence of GPS behaviour in pulsars surrounded by PWNe imparts further credence to this view. The pulsar J1747−2958 associated with the well-known Mouse nebula was also observed in our sample and exhibited GPS behaviour. The pulsar was detected as a point source in the high-resolution images. However, the pulsed emission was not seen in the phased-array mode. It is possible that the pulsed emission was affected by extreme scattering causing considerable smearing of the emission at low radio frequencies. The GPS spectra were modelled using the thermal free–free absorption and the estimated absorber properties were largely consistent with PWNe. The spatial resolution of the images made it unlikely that the point source associated with J1747−2958 was the compact head of the PWNe, but the synchrotron self-absorption seen in such sources was a better fit to the estimated spectral shape.